2005
DOI: 10.1191/0961203305lu2072oa
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal outcome of lupus pregnancy: a prospective study of 29 pregnancies

Abstract: The aim of this study was to analyse pregestational and pregnancy risk factors for adverse fetal and maternal outcome in lupus pregnancy. Twenty women with systemic lupus erythematosus (SLE) (29 pregnancies) were prospectively evaluated. Mean patient age was 29.5+/-4.7 years, and mean disease duration, 6.3+/-6.5 years. Twenty-two pregnancies (75.9%) ended in live births; preterm delivery occurred in 17.4%, intrauterine growth restriction in 50%, preeclampsia in 3.7%, and gestational hypertension in 8%. Six pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…3,13,14) Preeclampsia rate was 11.3% in our study, which falls within the range of 5-38% reported by previous reports. 3,15,16) There was no significant association between the occurrence of preeclampsia and dosage of corticosteroid or previous renal disease.…”
Section: Discussionsupporting
confidence: 74%
“…3,13,14) Preeclampsia rate was 11.3% in our study, which falls within the range of 5-38% reported by previous reports. 3,15,16) There was no significant association between the occurrence of preeclampsia and dosage of corticosteroid or previous renal disease.…”
Section: Discussionsupporting
confidence: 74%
“…The risk of maternal morbidity is increased in the setting of active LN (11,23,(44)(45)(46)(47), including an increased risk of hypertensive disorders of pregnancy (42). A recent metaanalysis reported frequencies of 16.3% for hypertension and 7.6% for pre-eclampsia among pregnant LN patients.…”
Section: Maternal Outcomesmentioning
confidence: 99%
“…Several prospective studies have suggested that the frequency of these flares may be lowest in the third trimester [28][29][30]. Reported rates of such flares range from 13.5-65% of pregnancies in affected women [31]. The frequency of flares during lupus pregnancies has been the subject of seven prospective comparative studies that have used nonpregnant lupus patients as controls (Table 2).…”
Section: Lupus Flares Associated With Pregnancymentioning
confidence: 99%